One-Time Cash Flow Announcements and Free Cash-Flow Theory: Share Repurchases and Special Dividends. - He, Jia; Howe, Keith M; Kao, G Wenchi (Journal of Finance, 1992)
The leading explanation for the positive price response surrounding tender offer share repurchase and specially designated dividend (SDD) announcements is the information signaling hypothesis. This paper reexamines these announcements to determine if Jensen's free cash-flow theory also has explanatory power. Lang and Litzenberger's (1989) findings suggest an important role for the free cash-flow theory in explaining the market's reaction to dividend changes. In contrast, they find the market's reaction to share repurchases and SDDs is approximately the same for both high-Q and low-Q firms. They thus have an empirical puzzle: If Jensen's free cash-flow theory applies to dividend changes, it is difficult to see why it does not also apply to the analogous events examined here.